2012
DOI: 10.4068/cmj.2012.48.2.116
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Melatonin on Retinal Ganglion Cell Survival in Ischemic Retina

Abstract: Our objective was to determine whether melatonin increases retinal ganglion cell (RGC) survival in ischemic mouse retina. Transient retinal ischemia was induced by an acute elevation of intraocular pressure in C57BL/6 mice. To evaluate the effect of melatonin on retinal ischemia, an equal amount of either melatonin or vehicle was intraperitoneally injected into the mice 1 hour before ischemia, at the time of ischemia, and 1 hour after ischemia. Hypoxia inducible factor 1α (HIF-1α) and glial fibrillary acidic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…HIF-1α has been determined to play vital roles in certain ischemic diseases, such as ischemic stroke, liver, kidney ischemia/reperfusion injury [66][67][68], and retinal ischemic injury [69], but the exact mechanisms in acute glaucoma remain unclear. Previous studies have demonstrated that HIF-1α can mediate NLRP3 inflammasome activation and IL-1β secretion [70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α has been determined to play vital roles in certain ischemic diseases, such as ischemic stroke, liver, kidney ischemia/reperfusion injury [66][67][68], and retinal ischemic injury [69], but the exact mechanisms in acute glaucoma remain unclear. Previous studies have demonstrated that HIF-1α can mediate NLRP3 inflammasome activation and IL-1β secretion [70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] In this study, we investigated the effect of transient ischemia in the retina 21 days after I/R, common model to investigate degenerative diseases of the retina. 18 We used a combination of ERG measurements and immunohistology to analyze the effects of ischemia on the different retinal cell types including RGCs, amacrine cells, bipolar cells, and glia cells. Additionally, we investigated apoptotic processes and the activation of phagocytes in the ischemic retina.…”
mentioning
confidence: 99%
“…Additionally, and in experimental models of optic neuritis and retinal ischemia, melatonin treatment inhibits glial reactivity and reduces the expression of hypoxia inducible factor ‐1α, COX‐2, and TNF‐α genes (Figure ) . It is, thereby, also acting as a neuroprotective agent.…”
Section: Melatonin and Aging‐related Eye Diseasesmentioning
confidence: 99%
“…[113][114][115]117 Additionally, and in experimental models of optic neuritis and retinal ischemia, melatonin treatment inhibits glial reactivity and reduces the expression of hypoxia inducible factor -1α, COX-2, and TNF-α genes (Figure 2). 241,242 It is, thereby, also acting as a neuroprotective agent. In relation to these effects, Jiang and colleagues have demonstrated that melatonin decreases the production of VEGF by Müller cells, the main retinal glial cells, under high glucose concentration.…”
Section: The Therapeutic Potential Of Melatonin In Glaucomamentioning
confidence: 99%